Evolution of the orbital angular momentum flux density of partially coherent vortex beams in atmospheric turbulence - Zhang, Yongtao; Yu, Jiayi; Gbur, Greg; Korotkova, Olga (Frontiers in Physics, 2022)
We investigate the behavior of the orbital angular momentum (OAM) flux density of partially coherent vortex (PCV) beams in atmospheric turbulence. It is shown that for PCV beams with different spatial coherence structures, the OAM flux density distribution exhibits rich variations along the propagation path. Our findings provide insight into the use of the OAM in free-space optical communications when turbulence effects are significant.